2019
DOI: 10.3389/fncel.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies Overlapping in Isolated Neurological Syndrome and Multiple Sclerosis: Neurobiological Insights and Diagnostic Challenges

Abstract: Antiphospholipid syndrome (APS) is characterized by arterial and venous thrombosis, pregnancy morbidity and fetal loss caused by pathogenic autoantibodies directed against phospholipids (PL) and PL-cofactors. Isolated neurological APS may represent a significant diagnostic challenge, as epidemiological, clinical and neuroimaging features may overlap with those of multiple sclerosis (MS). In an open view, MS could be considered as an organ-specific anti-lipid (phospholipid and glycosphingolipid associated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 129 publications
(151 reference statements)
0
17
0
Order By: Relevance
“…Antiphospholipid syndrome is an autoimmune disorder characterized by the presence of antiphospholipid antibodies, such as anticardiolipin antibodies, anti-β2-glycoprotein 1 antibodies, and lupus anticoagulant (Schreiber et al, 2018). APS neurological manifestations have been reported to be associated with some neurological diseases including ischemic stroke and MS (Ricarte et al, 2018; D’Angelo et al, 2019). Of note, cardiolipin is among the reported lipids antigens recognized by CD1d and this recognition may explain the increased number of NKT cells in some autoimmune diseases (Cox et al, 2009; D’Angelo et al, 2019).…”
Section: Nkt Cells and Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiphospholipid syndrome is an autoimmune disorder characterized by the presence of antiphospholipid antibodies, such as anticardiolipin antibodies, anti-β2-glycoprotein 1 antibodies, and lupus anticoagulant (Schreiber et al, 2018). APS neurological manifestations have been reported to be associated with some neurological diseases including ischemic stroke and MS (Ricarte et al, 2018; D’Angelo et al, 2019). Of note, cardiolipin is among the reported lipids antigens recognized by CD1d and this recognition may explain the increased number of NKT cells in some autoimmune diseases (Cox et al, 2009; D’Angelo et al, 2019).…”
Section: Nkt Cells and Neurological Diseasesmentioning
confidence: 99%
“…APS neurological manifestations have been reported to be associated with some neurological diseases including ischemic stroke and MS (Ricarte et al, 2018; D’Angelo et al, 2019). Of note, cardiolipin is among the reported lipids antigens recognized by CD1d and this recognition may explain the increased number of NKT cells in some autoimmune diseases (Cox et al, 2009; D’Angelo et al, 2019). Wermeling et al (2010) demonstrated that injection of apoptotic cells decreased the ability of type I NKT cells to produce cytokines, which further increased autoreactive B cells to produce autoreactive antibodies, such as anticardiolipin antibodies and antiphosphorylcholine, although this contrasts with the demonstration that NKT cells could promote B cell responses, and antibody production (Doherty et al, 2018).…”
Section: Nkt Cells and Neurological Diseasesmentioning
confidence: 99%
“…The diagnostic APS criteria are anticardiolipin (aCL), antiβ2glycoproteinI (aβ2GPI) and lupus anticoagulant (LA) [1,5]. APS can be classified only in the presence of thrombotic (noninflam matory arterial, venous or small vessel thrombosis) obstetric complications (death of one or more morphologically normal fetus at or beyond the 10 th week of gestation; one or more premature birth of normal fetus before the 34 th week due to eclampsia, pre-eclampsia or placental insufficiency), or increased aPL level [2].…”
Section: Introductionmentioning
confidence: 99%
“…aβ2GPI antibodies are central in pathogenic APS mechanisms and, although the full pathogenesis of APS is not clear yet, the binding of these aPL antibodies to the antigens on the cell surface of platelets, monocytes, endothelial cells and trophoblasts triggers intracellular signaling with subsequent activation and alteration of diverse cell functions. Cellular activation starts after the binding of the complex aβ2GPI antibody/β2GPI [5,7]. β2GPI is the most important antigenic target [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation